Sesquiterpene lactones of the eudesman type from artemisia semiarida: isolation and spatial structure - Turdybekov, K. M.; Rakhimova, B. B.; Turdybekov, D. M.; Adekenov, S. M. (Journal of Structural Chemistry, 2021)
As a result of studying the chemical composition of the Kazakh endemic Artemisia semiarida ((Krasch. Et Lavr.) Filat.), sesquiterpene γ-lactones of the eudesman type are isolated for the first time: taurine, 8α-acetoxytaurine, and 8α-hydroxytaurine. Their spatial structures are determined by X-ray diffraction (XRD). New eudesmanolide named 8α-acetoxy-2-en-taurine is also isolated. Based on the single crystal XRD data, its structure is 1-keto-8α-acetoxy-7α,6,11β(H)-eudesm-2,4-diene-6,12-olide.
Keywords: Artemisia semiarida; sesquiterpene lactones; eudesmanolides; taurine; 8α-acetoxytaurine; 8α- hydroxytaurine; 8α-acetoxy-2-en-taurine